Evaluation of a multiplex PCR method to serotype Salmonella in animal feeds pre-enrichment broth cultures - Junia Jean-Gilles Beaubrun; Laura Ewing; Kim Dudley; Faiza Benhamed; Hua Wang; Darcy E. Hanes (MethodsX, 2017)
The identification of Salmonella enterica serotypes remains a highly important public health concern for microbiological analysis of foods, feeds, and clinical samples. Outbreaks of human salmonellosis are sometimes linked to contact with infected animals and animal feeds. To possibly reduce the number of outbreaks, it is important to rapidly, efficiently detect Salmonella enterica in animal feeds and food products. A multiplex PCR for molecular serotyping of Salmonella enterica previously used in a single lab validation study for serotyping in multiple human food matrices was used in this investigation to evaluate the effectiveness of the multiplex PCR assay as serotyping method and screening tool for Salmonella in animal feeds. This approach is unique in that: • The multiplex PCR serotyping assay may be used for rapid screening and serotyping of Salmonella enterica from contaminated animal feed at the non-selective pre-enrichment step. • The assay may provide the serotype or identification of Salmonella in positive samples at concentration as low as 10 CFU/25 g after a 24 h non-selective pre-enrichment step. • In addition to the ability to serotype, this assay contains invA as an internal control for Salmonella positive identification. The invA shows positive indication for Salmonella outside of the 30 serotypic banding patterns.